Implementing a One Health village volunteer programme in West Sulawesi, Indonesia: A pilot study. Issue 11 (2nd November 2021) - Walton, Merrilyn; Arsyad, Dian Sidik; Alimuddin, Sarina; Arundhana, Andi Imam; Guest, David; McMahon, Peter; Doel, Rauf; Nasir, Sudirman
ABSTRACT : A pilot village volunteer programme (VVP) was implemented to produce new knowledge about the extent to which 24 trained village volunteers, taking an integrated One Health approach, could assist their communities by disseminating information on better agricultural and health practices. Just prior to the six-month pilot, the volunteers were mentored in a four-day training programme by local agricultural extension and public health experts. On returning to their villages, contacts and activities by volunteers with local community members were monitored using a CommCare application, enabling uploaded data to be accessed in real-time. The six volunteers in each village coordinated activities to address concerns of households. The VVP resulted in 960 actions (356 agricultural; 604 health), helping in 97% of contacts, most (55-61%) by providing information and others by advising community members where appropriate information could be sourced. Focus group meetings with village leaders, community health staff and local extension officers supported continuation of the VVP through local funding. Six months after the pilot, volunteers were continuing their activities and assisting with other government measures, such as district programmes to reduce childhood stunting and improve waste disposal. Community empowerment using local human resources is sustainable and could be supportive in government programmes.